North-South Dialogues in Forced Migration - McWeeny, Elizabeth (Refuge: Canada’s Journal on Refugees, 2007)
The following speech was given by Elizabeth McWeeny, President of the Canadian Council of Refugees, on the occasion of the opening of the tenth biennial conference of the International Association of the Study of Forced Migration, hosted by the Centre for Refugee Studies of York University in June 2006.